Pembelajaran Peta Konsep Untuk Membangun Pemahaman Siswa Pada Mata Pelajaran Akidah Akhlak Kelas Xi MA Al Fatah - Asna Bariroh , Asna; Rimatus Sholihah , Fiddini (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2022)
From this research, it is to find out the concept mas learning to build student’s understanding on the subjects of Akidah Akhlak in class XI MA AL-Fatah. The Approach used in this study is a Qualitative descriptive approach. Sources of research data obtained form student and teachers. Data collection techniques used are observation, interview, and Documentation. The results of the application of concept map learning, students look more active and can respond with more fokus when using teaching materials with concept map, as well as the motivation and creativity of students learning to be higher to understand the explanation during the learning process.